Nutrient Balance as a Tool for Maintaining Yield and Mitigating Environmental Impacts of Acacia Plantation in Drained Tropical Peatland—Description of Plantation Simulator - Laurén, Ari; Palviainen, Marjo; Page, Susan; Evans, Chris; Urzainki, Iñaki; Hökkä, Hannu (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Responsible management of Acacia plantations requires an improved understanding of trade-offs between maintaining stand production whilst reducing environmental impacts. Intensive drainage and the resulting low water tables (WT) increase carbon emissions, peat subsidence, fire risk and nutrient export to water courses, whilst increasing nutrient availability for plant uptake from peat mineralization. In the plantations, hydrology, stand growth, carbon and nutrient balance, and peat subsidence are connected forming a complex dynamic system, which can be thoroughly understood by dynamic process models. We developed the Plantation Simulator to describe the effect of drainage, silviculture, fertilization, and weed control on the above-mentioned processes and to find production schemes that are environmentally and economically viable. The model successfully predicted measured peat subsidence, which was used as a proxy for stand total mass balance. Computed nutrient balances indicated that the main growth-limiting factor was phosphorus (P) supply, and the P balance was affected by site index, mortality rate and WT. In a scenario assessment, where WT was raised from −0.80 m to −0.40 m the subsidence rate decreased from 4.4 to 3.3 cm yr−1, and carbon loss from 17 to 9 Mg ha−1 yr−1. P balance shifted from marginally positive to negative suggesting that additional P fertilization is needed to maintain stand productivity as a trade-off for reducing C emissions.
Keywords: carbon balance; forest drainage; fertilisation; growth; phosphorus; peatland forests; carbon; drainage; ecosystem modelling; peat subsidence; water table